Pembelajaran Tari Sisingaan: Pendidikan Berbasis Komunitas Di Kabupaten Subang - Soleha, Fitri (Jurnal Pendidikan Tari, 2021)
This paper is based on the results of researchers’ obsrvations about learning the Sisingaan dance at the Sisingaan Art Studio, Tresnawangi, Subang Regency as a form of community-based non-formal education. It can be seen that the learning of Sisingaan dance taught to children can help them become more active and positive in carrying out activites that can preserve and maintain the existence of Sisingaan dance. The purpose of this study is to identify and describe the concept of Sisingaan dance learning and the learning process of Sisingaan dance at the Sisingaan Art Studio Trenawangi. This research used descriptive qualitative approach. Data was collected by using observation, interviews, and documentation techniques. Datas were analyzed by data reduction techniques, data presentation, and drawing conclusions. The results of this study indicate that the Sisingaan Dance learning at the Sisingaan Art Studio in Tresnawangi has a dance learning concept with the aim of emphasizing participats’ learning on learning materials about Sisingaan dance, so that participats learn to master the techniques and movements in dance. The learning process of Sisingaan Dance in delivering material uses several learning methods including lecture, demonstration, imitation, and drill / practice methods.